2021
DOI: 10.1289/ehp7396
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Estimation of Endogenous Biomarker Associations with Prenatal Phenols, Phthalates, Metals, and Polycyclic Aromatic Hydrocarbons in Single-Pollutant and Mixtures Analysis Approaches

Abstract: Background: Humans are exposed to mixtures of toxicants that can impact several biological pathways. We investigated the associations between multiple classes of toxicants and an extensive panel of biomarkers indicative of lipid metabolism, inflammation, oxidative stress, and angiogenesis. Methods: We conducted a cross-sectional study of 173 participants (median 26 wk gestation) from the LIFECODES birth cohort. We measured exposure analytes of multiple toxicant classes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…We also examined potential correlations among workers' traits linked to oxidative stress and tumor biomarkers. Earlier studies only assessed the impact of PAHs and heavy metals on oxidative stress levels, and the results were inadequate and contradictory [ 5 ]. A study of pregnant women reported that urinary hydroxylated PAHs and metal mixes were positively correlated with 8-hydroxyguanosine (8-OHdG) but not in the same way with 8-iso-prostaglandin F2α [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also examined potential correlations among workers' traits linked to oxidative stress and tumor biomarkers. Earlier studies only assessed the impact of PAHs and heavy metals on oxidative stress levels, and the results were inadequate and contradictory [ 5 ]. A study of pregnant women reported that urinary hydroxylated PAHs and metal mixes were positively correlated with 8-hydroxyguanosine (8-OHdG) but not in the same way with 8-iso-prostaglandin F2α [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies only assessed the impact of PAHs and heavy metals on oxidative stress levels, and the results were inadequate and contradictory [ 5 ]. A study of pregnant women reported that urinary hydroxylated PAHs and metal mixes were positively correlated with 8-hydroxyguanosine (8-OHdG) but not in the same way with 8-iso-prostaglandin F2α [ 5 ]. PAHs have shown metabolic stimulation to form free radical mediates that endure redox cycling to produce ROS, which is bound covalently to biomolecules such as lipids, proteins, and DNA, leading to lipid peroxidation, the creation of protein and DNA adducts, oxidative stress, and DNA alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The least absolute shrinkage and selection operator (LASSO) regression model was used to minimize a large number of variables in the model and, importantly, had the unique feature of penalizing the absolute value of a regression coefficient [ 20 , 21 ]. The regression coefficient of the regression model was based on the value of λ (λmin or λ1se).…”
Section: Methodsmentioning
confidence: 99%
“…The pathways by which phthalates may adversely affect pregnancy are not fully understood. Our previous work has shown significant associations between increased exposure to phthalates during pregnancy and various thyroid and reproductive hormones, 21 as well as biomarkers of oxidative stress, 22 , 23 inflammation, 22 , 24 , 25 and lipid metabolism, 25 which are all important for maintaining a healthy pregnancy. Phthalates may exert deleterious effects on pregnancy through disruption of these physiological processes.…”
Section: Introductionmentioning
confidence: 99%